The Normans power, conquest and culture in 11th-century Europe - Green, Judith A. (Yale University Press, 2022)
Frontmatter -- Contents -- Plates, Maps and Genealogical Tables -- Preface -- Introduction -- 1. Writing about the Normans -- 2. The Making of Ducal Normandy -- 3. Swords for Hire -- 4. Normans in the South -- 5. Normans in Britain -- 6. The First Crusade and the Principality of Antioch -- 7. The Normans and Power -- 8. The Normans and the Church -- 9. Encounters -- 10. Buildings -- Conclusion -- Endnotes -- Maps and Genealogical Tables -- Bibliography -- Index
Keywords: Geschichte 1000-1100; Normannen; Europa; Normans / History / To 1500; HISTORY / Europe / Great Britain / Norman Conquest to Late Medieval (1066-1485)